Malaysian transverse rumble strips: a review and recommendations for practice - Othman, Mohd. Hanifi (Penerbit UTM Press, 2015)
Transverse rumble strips (TRS) is a common choice to reduce vehicle speed and increase driver alertness on roadway. TRS is a series of marked (either flat or raised) transverse bars placed across the road in direction of traffic flow. It functions to assist driver to become aware through optical, vibration and audible effect thus encouraging drivers to reduce speed and increase their alertness in order to face any hazard that may exist ahead. Although often being used, in reality TRS usage in Malaysia still has some aspects that can be improved. The purpose of this paper is to critically review the definition of thermoplastic TRS, its effectiveness, standard guidelines in Malaysia, thermoplastic materials and colour and also to propose the recommendation in regard practice of TRS in order to increase its effectiveness. Besides the available literature source in the light of the latest published findings, personal interview have been done to several authorities which are headquarter and district public work department, local municipal and university regarding TRS application guidelines and practice in Malaysia. The authors synthesize the available findings on the TRS performance and standard guidelines to propose some recommendations for a better application practice of TRS in particular in Malaysia. The proposal of all the findings hopefully would be beneficial to authorities in improving the practices of TRS.